INTEGRATED ASSESSMENT OF ENVIRONMENTAL AND ECONOMIC EFFICIENCY OF GAS BOILER OPERATING MODES: Array - Ponomarenko, Y.; Katkov, M.; Semenenko, R. (Municipal economy of cities. Series: «Economy science», 2020)
A thermal energy is one of the most significant sources of environmental impact.This is a consequence of both the use of mostly non-renewable natural resources and environmental pollution from thermal power plants. The intensity of this impact depends on many factors, namely the purpose, power, type of fuel used and operating mode. Existing studies have established links between emissions and characteristics such as power and fuel type for stationary operating conditions. At the same time, changes in operating conditions have a significant impact on environmental and economic characteristics. This article is devoted to establishing the relationship between the operational characteristics of gas boilers and their environmental and economic efficiency. The analysis was based on the field data obtained from steam and water boilers that are in commercial operation and uses the natural gas. It was found that for steam and water boilers, there is a well-conditioned non-linear relationship between the technological parameters of boiler operation, in particular gas consumption, the percentage of boiler load, the amount and temperature of flue gases with indicators of pollutants entering the atmosphere. The most significant factor affecting the environmental and economic characteristics of boilers is the percentage of load of boilers. The nature of the dependency is determined by the type of boiler and the setting mode. These dependences with a high degree of conditionality have a parabolic character, which makes it possible to assume the existence of adjustment modes that minimize environmental and economic costs. For steam and water boilers, the dependence of environmental impact on the percentage of load is direct. But for steam boilers in the range of data that were studied, it has a monotonous character, that is, it does not have an extremum point. For water boilers, it is possible to find the optimal loading level that minimizes environmental costs, but to confirm this assumption, additional research is needed at low boiler loading levels. The proposed method can be used to determine the operating modes of boilers and their settings, taking into account environmental and economic criteria.